Pemberantasan Hama Tikus: Potensi dan Strategi KKN di Desa Pagedangan, Indramayu, Jawa Barat - Arwani, Arwani (Kusuma: Jurnal Pengabdian kepada Masyarakat, 2024)
This community service program, "Rodent Pest Eradication in Farmers' Agricultural Fields," was designed and implemented as a potential and strategic focus for the Community Service Program (KKN) in Pagedangan Village, Tukdana Subdistrict, Indramayu Regency, West Java. Recognizing the significant agricultural landscape of the region and the detrimental impact of rodent pests on crop yields and farmers' livelihoods, this KKN initiative aimed to empower the community with sustainable solutions. The program involved a comprehensive situation analysis, educational workshops on rodent biology and integrated pest management, practical training on constructing and utilizing eco-friendly traps, and the establishment of farmer groups for collaborative action. Furthermore, it fostered partnerships with local agricultural agencies and explored environmentally sound pest control methods. The expected outcomes include increased farmer knowledge, adoption of effective pest management techniques, a reduction in rodent populations, improved crop productivity, and enhanced community resilience towards agricultural challenges. This KKN model demonstrates the potential of student engagement in addressing critical agricultural issues at the grassroots level, contributing to food security and rural development.